Plan de negocios para la creación de una sala velatoria en la parroquia Malacatos de la provincia de Loja - Mancheno Luzuriaga, Larry Michael (2016)
This research has been developed in Loja, specifically in Malacatos parish, the proposal is to implement a joint funeral services for the population, in order to conduct a socio-economic strengthening of the parish. The introduction makes a general analysis of the areas where microenterprises will be developed. Reviewing of the literature consists of the history of funeral service in the evolution in time, as the theoretical concepts that we´ll use in the development of the research. Materials and methods: analyze the materials and methods used for the data collection techniques that were used to present the results. Analyzing the results of surveys of 315 people from a total of 7632 habitants of the parish, also the various techniques and methods were obtained and confirmed by accurate conclusions of potential users and competitions that may arise. Furthermore, these results allow the study of the market and technical and financial study. The annual average use of the funeral services to be provided in the parish Malacatos was done through surveys of the habitants regarding the frequency rate or the mortuary average index, resulting in 60 deaths annually. Furthermore, the analysis of the offer and demand allowed us to determine the unmet demand, it is necessary to notice that the demand of the parish is about 42 and the annual service is 60. Thus the unmet demand is 42. The service will be open 24 hours a day, 7 days a week, and 365 days a year to satisfy the needs of the residents and to optimize its operation in order to provide a quality service. The service charge will be $1.063,00 for services with a profit margin of 35,00%, it has been determined according to the costs involved in putting it into the market, on the other hand, considering that people seek payment facilities there is pretended to arrange the collection mode by paying the 50,00% cash and 50,00% split into three monthly instalments of charge. Likewise, the advertising will be limited by the fact that most media in the parish, so the company will put an illuminated sign which projects and publish the image of the company and also the radio spots through the radio that there is in this place. The capacity of use for the service will be 60 which correspond to 100,00% of installed capacity and the service will be unique in the parish, realizing that the existing funeral home is only for the exclusive use of members of the funeral and not a service for the whole population. The amount needed for the implementation of the funeral home is $26.056,96 and this will be funded as follows: 63,00% will be financed through a financial institution that means that the amount will be $16500,00, while 37,00% will be funded by shareholders and the amount will be $9.556,96 The company is legally constituted, will be formed by a limited liability company. The company will have duration of 5 years from the date of registration of the contract, establishing the commercial register. The management and administration of the company is exercised through the following bodies: the general meeting, the president and general manager. Likewise the equilibrium point for the first year in terms of installed capacity was determined in 67,97% and in terms of sales $30.332,46 reaching the value at which the firm equals the value of their costs and expenses. The financial evaluation will indicate whether the project is executable or not, the application of various financial rates such as: as the financial analysis the net present value of the project (NPV) is $4.025,13 which ensures a return on the value of the company at the end of life. The internal valuation of return (TIR) is 15,00% which is above the interest rate of 10,00%. The benefit cost is $ 1,15 which is favourable; it indicates that for every dollar it is possible to get $ 0,15 profit. The capital recovery period is 4 years, 7 months and 16 days; also the project agreed an increase in the costs up to 17,68% and a decrease in incomes of a 10,85%. Thus, the results of the investigation demonstrate the feasibility for the implementation of the project, ensuring profitability for investors and on the other hand, allow a socio-economic business development in the parish Malacatos, and are a source of employment which will improve the living standards of people in the sector.